Analisa Pengaruh Sense Experience dan Store Atmosphere terhadap Minat Beli Ulang Konsumen dengan Kualitas Layanan sebagai Variabel Moderasi - Dhentar Eka Pratama (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
This study aims to find out the Sense Experience and Store Atmosphere factors in influencing consumer Repurchase Interest which is moderated by Service Quality. In this case the researcher will find out how much influence the independent variable has on the dependent individually and collectively. The research was conducted at the Klinik Kopi Yogyakarta. The data were obtained from a questionnaire that was distributed directly to customers of Kedai Klinik Kopi who happened to be met at the location. Then the researcher processed the data using the SPSS application which generated numbers and could be explained in response to the hypothesis and problem formulation of this study.